Efficacy and Safety of Colchicine in Post–acute Myocardial Infarction Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Diaz-Arocutipa, Carlos; Benites-Meza, Jerry K.; Chambergo-Michilot, Diego; Barboza, Joshuan J.; Pasupuleti, Vinay; Bueno, Héctor; Sambola, Antonia; Hernandez, Adrian V. (Frontiers in Cardiovascular Medicine, 2021)
Background: Inflammation plays a key role in atherosclerotic plaque destabilization and adverse cardiac remodeling. Recent evidence has shown a promising role of colchicine in patients with coronary artery disease. We evaluated the efficacy and safety of colchicine in post-acute myocardial infarction (MI) patients. Methods: We searched five electronic databases from inception to January 18, 2021, for randomized controlled trials (RCTs) evaluating colchicine in post-acute MI patients. Primary outcomes were cardiovascular mortality and recurrent MI. Secondary outcomes were all-cause mortality, stroke, urgent coronary revascularization, levels of follow-up high-sensitivity C-reactive protein (hs-CRP), and drug-related adverse events. All meta-analyses used inverse-variance random-effects models. Results: Six RCTs (n=6005) patients were included. Colchicine did not significantly reduce cardiovascular mortality (risk ratio [RR], 0.91; 95% confidence interval [95%CI], 0.52-1.61; p=0.64), recurrent MI (RR, 0.87; 95%CI, 0.62-1.22; p=0.28), all-cause mortality (RR, 1.06; 95%CI, 0.61-1.85; p=0.78), stroke (RR, 0.28; 95%CI, 0.07-1.09; p=0.05), urgent coronary revascularization (RR, 0.46; 95%CI, 0.02-8.89; p=0.19), or decreased levels of follow-up hs-CRP (MD, -1.95 mg/L; 95%CI, -12.88 to 8.98; p=0.61) compared to the control group. There was no increase of any adverse event (RR, 0.97; 95%CI, 0.89-1.07; p=0.34) or gastrointestinal adverse events (RR, 2.49; 95%CI, 0.48-12.99; p=0.20). Subgroup analyses by colchicine dose (0.5 versus 1 mg/day), time of follow-up (<1 versus ≥1 year), and treatment duration (≤30 versus >30 days) showed no changes in the overall findings. Conclusion: In post-acute MI patients, colchicine does not reduce cardiovascular or all-cause mortality, recurrent MI, or other cardiovascular outcomes. Also, colchicine did not increase drug-related adverse events.